Pentingnya Teologi Pendidikan Agama Kristen Dalam Pembentukan Karakter Anak - Agustinus Tandilabi; Ester Novitadesy; Sandra Rosiana Tapilaha (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
This research aims to explain to us the importance of Christian religious education theology in shaping children's character. By being based on moral values ​​and religious principles, Christian religious education provides a solid foundation for children's spiritual growth. Through a deep understanding of love, compassion, integrity, and responsibility, children can develop strong and responsible characters in the future. The research method used is literature analysis from theological and educational sources, as well as tracing empirical studies that support the relationship between Christian religious education and the formation of children's character. The results of this research indicate that Christian religious education plays a key role in shaping children's character, by providing a sustainable moral framework for their growth and development. The practical implication of this research is the importance of integrating religious values ​​in children's education to ensure sustainable and holistic character formation.